PC-APC Schemes in Multipath Diversity System to Get Higher Throughput - Sanjit Ningthoujam; Manash Pratim Dutta; Subhasish Banerjee; Chandan T. Bhunia; Swarnendu K. Chakraborty (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper is studied about a new protocol of Packet combining (PC) and Aggressive Packet Combining Scheme (APC) in multipath diversity system to get higher throughput. In the proposed protocol of PC and APC schemes, two and three copies of a packet are sent in two and three paths. If either of the copies is received without any erroneous then select the correct one and discard all other copies.  Again if all copies are found as erroneous then combine the erroneous copies and perform XOR operation in case of PC and bit by bit majority logic in case of APC in order to get the original copy. The paper is implemented using Mat lab and found that new proposed protocols are getting higher throughput and probability of receiving successful packet at the receiver side. Thus, performance of error prone wireless network can be improved by applying either PC or APC in multipath diversity system.